ENGLISH STUDENTS’ PERSPECTIVES ON THE USE OF TAYLOR SWIFT SONGS FOR VOCABULARY DEVELOPMENT - Julia Stephanny; Yohana Triana Ina Weran (Suluh Adiluhung Publisher (SAPub), 2026)
Numerous studies have demonstrated that students' vocabulary acquisition improves more effectively when learning occurs through meaningful and practical experiences, such as watching movies, reading stories, or listening to songs, particularly in English. Song-based learning is often perceived as both engaging and enjoyable by learners. This study aims to explore English students' perspective on the use of Taylor Swift's songs as a medium for vocabulary development. The participants were fourth semester English students at Kapuas University, Sintang, with a total of nine students involved in the study. This research employed a descriptive qualitative design. Data were collected through an online questionnaire distributed to the participants. The findings indicate that Taylor Swift’s songs have the potential to serve as an effective medium for enhancing students’ vocabulary.